Colour-tunable asymmetric cyclometalated Pt(ii) complexes and STM-assisted stability assessment of ancillary ligands for OLEDs. Issue 13 (11th March 2016) - Sanning, Jan; Stegemann, Linda; Ewen, Pascal R.; Schwermann, Christian; Daniliuc, Constantin G.; Zhang, Dongdong; Lin, Na; Duan, Lian; Wegner, Daniel; Doltsinis, Nikos L.; Strassert, Cristian A.
Abstract : The DFT-guided and STM-assisted realization of tunable triplet emitters is reported. Abstract : We combined an asymmetric cyclometalated C^N^N Pt(ii ) complex with three different classes of monodentate ancillary ligands, namely a bulky phosphine, a tilted pyridine, and either a tilted or a coplanar isocyanide. The controlled planarization of the coordination environment yields green, orange or red phosphors. Electronic structure calculations using DFT reveal the excimeric intermolecular interactions in the excited triplet state, resulting in tunable photophysical properties. Finally, we assess the suitability of the ancillary ligands for optoelectronic applications by investigating the molecular integrity upon sublimation with the aid of scanning tunneling microscopy (STM). The ancillary ligand controls the surface-induced chiral self-assembly of the molecules on metallic substrates, as well as the availability of loose coordination sites. The concordance between the photoluminescence spectra and electroluminescence profiles for solution-processed and vapour-deposited devices confirm the predictions attained by STM regarding molecular integrity and processability.